The Promotive Effect of Putrescine on Growth, Biochemical Constituents, and Yield of Wheat (Triticum aestivum L.) Plants under Water Stress - Hebat-Allah A. Hussein; Shifaa O. Alshammari; Marwa E. Abd El-Sadek; Sahar K. M. Kenawy; Ali A. Badawy (Agriculture, 2023)
Drought stress is a significant environmental variable affecting wheat growth and development. Plant stress tolerance is intimately related to growth regulators of plants as polyamines. The study assessed the impact of drought (50% water irrigation and 100% water irrigation), priming of grains in putrescine (0.25, 0.5, and 1 mM), and their interactions on the growth, yield, and physiological attributes of wheat plants. Drought conditions declined plant height, fresh and dry weights, leaves and tillers numbers, and flag leaf area. However, applying putrescine, especially at (1 mM), enhanced wheat growth performance in normal or water-deficit conditions. Drought stress decreased spike length (28.6%), number of spikelets (15.6%), number of grains (30.3%), the weight of the spike (23.5%), and the weight of the grains/spike (37.5%). In addition, drought decreased the contents of chlorophyll a, chlorophyll b, free amino acids, and total phenols, while applying putrescine enhanced wheat plant growth performance in normal or drought conditions. Putrescine at (1 mM) achieved the highest increase in plant height (38.8%), root length (50%), leaves number (166%), tillers number (80%), flag leaf area (70.3%), shoot fresh weight (99.4%), shoot dry weight (98.4%), root fresh weight (97.8%), root dry weight (210%) compared to the untreated plants. Moreover, pretreatment with putrescine improved chlorophyll a (13.3%), chlorophyll b (70.3%), carotenoids (61.8%), soluble sugars (49.1%), amino acids (42.7%), phenols (52.4%), number of spikelets (59.3%), number of grains (81.1%), and weight of spike (45.4%). Moreover, variations in the protein profile of wheat plants were due to drought conditions and putrescine application. In conclusion, priming wheat grains with putrescine effectively induces protective mechanisms against water stress and improves wheat plants’ physiological attributes and yield components.